Nutrient Quality and in Vitro Digestibility of Bio-Ammoniated Rice Straw Bales - Cuk Tri Noviandi; Dibya Ratnopama; Ali Agus; Ristianto Utomo (Faculty of Animal Science, Universitas Gadjah Mada, 2020)
This study was done to determine the effects of bale sizes of bio-ammoniated rice straw on its nutrient quality and in vitro digestibility. Rice straw were bio-ammoniated by adding 2 g urea and 1 g probiotic/kg DM. By following a completely randomized design, rice straw was baled in 3 different weights (15, 25, and 35 kg) with six replications for each treatment, and then stored for 3 weeks. In the end of the week 3, bales were opened, aired, and then sampled for proximate analysis (dry matter, organic matter, crude protein, and crude fiber) and digestibility by in vitro gas production method. Using analysis of variance method, the proximate data showed that greater the bales size (15, 25, and 35 kg) increased crude protein (7.59, 7.86, and 9.95%, respectively; P<0.05) and decreased crude fiber contents (24.1, 22.1, and 18.8%, respectively; P<0.05). By increasing the size of bales also increased a, b, and c fractions (-0.79, 0.26, and 0.82 mL/100 mg DM; 20.2, 18.2, and 17.6 mL/100 mg DM; 0.012, 0.014, and 0.019 mL/h, respectively; P<0.05) as well as gas production (11.4, 11.5, and 13.8 mL/100 mg DM, respectively; P<0.05). It can be concluded that packing bio-ammoniated rice straw in 35 kg bale is the most effective way in increasing nutrient quality and digestibility of rice straw.